Public Service Innovation in The Program of Bupati Ngantor di Desa in Banyuwangi Regency - Anggi Yuprita Amanda Puteri; Zarah Puspitaningtyas; Bagus Sigit Sunarko; Jamaluddin Jamaluddin (Jurnal Ad'ministrare, 2023)
Public service is an activity or series of activites in the contex of providing service needs in accordance with statutory regulations for every citizen and resident regarding goods, service and administrative services provided by public service provides. This study aims to determine the management of public service innovation through the Bupati Ngantor di Desa (Bunga Desa) program in Banyuwangi Regency. The research location is in Watukebo Village, Wongsorejo District. The focus of the related research is the management of public service innovation. For this reason, researchers use the New Public Management paradigm, Stewardship Theory, and Elements of Service Management. In the Program of ‘Bunga Desa,’ various problems were resolved in one day, including population administration, issuance of Nomor Izin Berusaha (NIB), and payment of Pajak Bumi dan Bangunan (PBB). The study results show that public service innovation management has succeeded in providing better service to the community. However, the record shows that the Government of Banyuwangi Regency has strengthened the rules regarding implementing the Bupati Ngantor di Desa so that this program has straightforward implementation operational standards, monitoring, and evaluation can be carried out after the program ends. This research can be used as a reference for decision msking in public services, bacause previous research focused more on the services of an agency.